Students' Mathematical Literacy on The Performance of PISA Questions: What Is Gender Correlation? - Harfin Lanya; Moh Zayyadi; Sitti Karimah Sulfiah; Abdul Roziq (Universitas Syiah Kuala, 2021)
Descriptive research with a qualitative approach method is used because it is accordance with the research objectives, namely to describe students' mathematical literacy towards the performance of the PISA questions in terms of gender. The subjects in this study were two students that 1 male and 1 female in the high math ability of category in grade 9 of junior high schools. Subjects were selected by purposive sampling by giving a mathematical ability test to 25 students to see their mathematical abilities, then also taking into account the mathematics teaching teacher, two students were obtained as research subjects in accordance with the purpose of the study, namely to describe students' mathematical literacy based on gender, especially students with high mathematical abilities.The instrument used was a mathematical ability test and a mathematical literacy test as well as an interview guide as research data. Based on data analysis, there is an influence of gender on students mathematical literacy level. Females mathematical iteracy is better than males mathematical literarcy, so there needs to be efforts to improve learning from both teachers and schools so that there are no longer differences in abilities between male and female, and gender does not affect mathematical literacy.